ESG Risk Ratings, Financial Performance And Corporate Value: The Case Of The Indonesia Stock Exchange - Marianus Hendrilensio Sanga; Situmorang, Resvina; Yessi Susan Intan P. Benu; Titian Jelita Tuka; Noble Sam Prince (Jurnal Ekonomi, 2024)
This research aims to examine the impact of ESG risk ratings provided by Sustainalytics on corporate value in Indonesia. The study focuses on companies listed on the Indonesia Stock Exchange in 2023, with ESG risk ratings as the independent variable and control variables such as corporate size, leverage, and liquidity. The purpose of this research is to assess how ESG factors influence corporate financial performance, with Return on Assets (ROA) and Tobin’s Q used as proxies for corporate value. The research utilizes a multivariate regression analysis with a cross-sectional data approach, employing Stata 17 software for data processing and analysis. The results indicate that ESG risk ratings have a significant positive impact on corporate value, suggesting that companies with higher ESG ratings generally exhibit higher corporate value. Additionally, corporate size and ROA were found to have a positive effect on corporate value, while leverage and liquidity were not statistically significant in this model. This study contributes to the existing body of literature by providing new insights into the role of ESG factors in shaping corporate value, especially in emerging markets such as Indonesia. The practical implications of these findings suggest that both companies and investors should take ESG factors into account when making investment decisions. Moreover, the results emphasize the importance of improving transparency in ESG reporting, as it can help reduce risks and uncertainties for stakeholders, leading to better decision-making and encouraging more sustainable business practices. This research highlights the growing relevance of ESG considerations in modern corporate governance.